Dualitat grafica e ensenhament de l’occitan provençal - François Courtray (Lengas)
One of the characteristics of the Provençal Occitan is that it can be spelt according to two rival written standards, i.e. the classic and Mistralian orthography. As indicated by the results of an investigation conducted among some teachers of the Aix-Marseille and Nice educational districts, this written duality is currently widespread among teachers and influences not only their representation but also their written language ability, the way they convey it and the educational tools they use, with important variations according to the orthographic system they adopt.